Developing Critical Thinking Skills and Early Childhood Creativity through The National Geographic Kids App - Anisa, Ahbib; Asmawulan, Tri (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the improvement of critical thinking skills and creativity in early childhood through the use of the National Geographic Kids digital application as an interactive learning medium in KB & Kindergarten Aisyiyah Pracimantoro. This research also aims to understand how the integration of digital media can create meaningful learning experiences that are appropriate for the development of children aged 5-6 years.Methodology: This study used a descriptive qualitative approach involving 14 children of group B (7 boys and 7 girls), one classroom teacher, and five parents as supporting informants. The activity lasted for six weeks (September-October 2025) in three learning phases, namely introduction, exploration, and reflection. Data were collected through participatory observation, in-depth interviews, documentation of children's work, and Focus Group Discussions (FGDs). Data analysis is carried out through the process of condensation, presentation, and drawing conclusions.Results: This study showed significant improvements in two main aspects. Critical thinking skills increased from 35.7% to 92.8%, indicated by the child's ability to ask questions, cause and effect reasons, and draw logical conclusions. Creativity increased from 28.6% to 78.6%, as seen in children's ability to produce original visual works and add personal ideas in drawing and digital games. The results of the FGD confirmed an increase in the child's focus, motivation, and active participation during the learning process.Application/Originality/Value: This research makes a practical contribution to the development of early childhood learning through the application of targeted and interactive educational digital media. The National Geographic Kids app has proven to be effective in stimulating children's critical thinking and creativity through a fun and contextual approach to exploration.